2022
DOI: 10.3390/cancers14051188
|View full text |Cite
|
Sign up to set email alerts
|

Border Line Definition Using Hyperspectral Imaging in Colorectal Resections

Abstract: Background: A perfusion deficit is a well-defined and intraoperatively influenceable cause of anastomotic leak (AL). Current intraoperative perfusion assessment methods do not provide objective and quantitative results. In this study, the ability of hyperspectral imaging (HSI) to quantify tissue oxygenation intraoperatively was assessed. Methods: 115 patients undergoing colorectal resections were included in the final analysis. Before anastomotic formation, the bowel was extracted and the resection line was ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In another study 49 , Jansen-Winkeln et al imaged colorectal tumors in 54 consecutive patients during colorectal resections and found that HSI used in combination with a neural-network algorithm was able to classify cancer or adenomatous margins around the central tumor with a sensitivity of 86% and a specificity of 95%. Recently, they published a large study 50 enrolling 115 patients who underwent colorectal resection to systematically assess the feasibility of HSI in quantifying tissue perfusion, and in accordance with a smaller patient series, they found that "well-perfused areas were clearly distinguishable from the less perfused ones only after one minute". 46,47 Similar conclusions were reached in a group of 52 patients undergoing colorectal surgery by Barberio et al 51 , who also found that the physiological HSI parameter StO 2 was significantly lower in patients receiving neoadjuvant radio/chemotherapy than in other oncological patients.…”
Section: Lower Gastrointestinal Tractmentioning
confidence: 89%
See 2 more Smart Citations
“…In another study 49 , Jansen-Winkeln et al imaged colorectal tumors in 54 consecutive patients during colorectal resections and found that HSI used in combination with a neural-network algorithm was able to classify cancer or adenomatous margins around the central tumor with a sensitivity of 86% and a specificity of 95%. Recently, they published a large study 50 enrolling 115 patients who underwent colorectal resection to systematically assess the feasibility of HSI in quantifying tissue perfusion, and in accordance with a smaller patient series, they found that "well-perfused areas were clearly distinguishable from the less perfused ones only after one minute". 46,47 Similar conclusions were reached in a group of 52 patients undergoing colorectal surgery by Barberio et al 51 , who also found that the physiological HSI parameter StO 2 was significantly lower in patients receiving neoadjuvant radio/chemotherapy than in other oncological patients.…”
Section: Lower Gastrointestinal Tractmentioning
confidence: 89%
“…Based on this literature review, the following inferences could be made: HSI is still finding its place in oncological clinical applications with the assessment of (i) mastectomy skin flap perfusion after breast reconstructive surgery 8 and (ii) anastomotic perfusion during reconstruction of gastrointenstinal conduit 9,44,45,[48][49][50] as the most promising. However, caution needs to be advised because recently much research has been done in the arena of using HSI during brain surgery for glioblastoma, yet this clinical effort has not been sustained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jansen-Winkeln [73] found that in 115 patients with colorectal resections, intraoperative HIS (hyperspectral imaging) was safe, repeatable, and not disruptive to the surgical process. Additionally, it assesses the surface perfusion of the gut.…”
Section: Studies Quantifying Perfusion Through the Association With F...mentioning
confidence: 99%
“…The combined application of ICG-FA and HSI within a single imaging system could provide supportive and complementary information regarding tissue vascularization, reduce perioperative mortality, and shorten surgical procedures. Jansen-Winkeln [61] found that , in 115 patients undergoing colorectal resections, intraoperative HIS(hyperspectral imaging) is safe, reproducible, and does not interfere with the surgical workflow. In addition, it measures bowel surface perfusion.…”
Section: Studies That Intent Quantification Of Perfusion Through the ...mentioning
confidence: 99%